Unicystic ameloblastoma with the presence of dentin - Sivapathasundharam B; Einstein A (Wolters Kluwer Medknow Publications, 2007)
We present a case of unicystic ameloblastoma of the posterior mandible in a 28 year-old female, histologically showing luminal and intramural plexiform epithelial proliferation with typical dentin in the connective tissue capsule. The characteristics of hard tissue formation in ameloblastomas reported in existing literature and the possible origin of the dentin mass seen in our case are discussed.